Factographic information system of multimedia database - Азаренко, О. В.; Куклінський, М. В.; Клімова, А. С. (Science-based technologies, 2018)
The article provides a solution to the problem of improving the efficiency of managing multimedia objects that are stored in the database. The use of factographic information systems is considered as a solution, and not only for the implementation of reference functions, but also for solving data processing tasks such as data entry, storage, sorting, searching and structuring. The article discusses the main problems encountered in the design of databases with multimedia content. These problems are usually caused by characteristics that are inherent only in multimedia data. It is with these characteristics in mind that the use of NoSQL as an additional technology for the implementation of a multimedia database, the application of the data warehouse concept and a hierarchical structure with nested sets is proposed along with the factographic information system. The proposed approaches will create conditions for improving the performance of the information systems of multimedia databases necessary for the presentation of the final results presented by users.